2019
DOI: 10.1007/s11307-019-01320-x
|View full text |Cite|
|
Sign up to set email alerts
|

Imaging of Tumor Spheroids, Dual-Isotope SPECT, and Autoradiographic Analysis to Assess the Tumor Uptake and Distribution of Different Nanobodies

Abstract: Purpose Recent studies have shown rapid accumulation of nanobodies (NBs) in tumors and fast clearance of the unbound fraction, making NBs exceptional tracers for cancer imaging. In this study, we investigate the combination of in vitro imaging of tumor spheroids, in vivo dual-isotope single-photon emission computed tomography (SPECT), and ex vivo autoradiographic analysis of tumors to efficiently, and with few mice, assess the tumor uptake and distribution of different NBs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 23 publications
(37 reference statements)
3
32
0
Order By: Relevance
“…However, in the context of this study, no significant differences were observed compared to 7D12-PS ( Figure S4). Together with the fact that the monovalent nanobody format is expected to distribute more homogenously than a bivalent format [11], this study was focused on one conjugate only, i.e., 7D12-PS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the context of this study, no significant differences were observed compared to 7D12-PS ( Figure S4). Together with the fact that the monovalent nanobody format is expected to distribute more homogenously than a bivalent format [11], this study was focused on one conjugate only, i.e., 7D12-PS.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a NB for PDT brings a series of advantages over antibody-targeted PDT. Their small size enables rapid tumor accumulation, with a homogeneous distribution, and a rapid clearance from circulation when unbound [9][10][11]. In the context of PDT, this allows the application of the light shortly after conjugate administration, ensures more extensive tumor damage, and reduces the chances of phototoxicity present in both PDT and antibody-targeted PDT protocols.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7D12 and R2 were expressed, purified by IMAC and conjugated to indicated dyes as described elsewhere (Oliveira et al 2012 ; Beltrán Hernández et al 2019 ). In short, his-tagged nanobodies were expressed in E. coli and purified from the periplasmic fraction by TALON purification and reconstituted in PBS.…”
Section: Preparation Of Isotope-labelled Spheroidsmentioning
confidence: 99%
“…Moreover, our experiments reveal that isotope-enrichment of amino acids in spheroids is readily achieved using a standard culture medium. Finally, we adapted our earlier procedures (Beltrán Hernández et al 2019 ) to study the [ 13 C, 15 N]-labelled anti-EGFR nanobody 7D12 (Roovers et al 2011 ) after penetration into the spheroids using sensitivity-enhanced DNP-ssNMR. Our data highlight the potential of conducting ssNMR-based studies on 3D cell cultures that in the future may reveal structure–function relationship of proteins in their native 3D cell microenvironment.…”
Section: Introductionmentioning
confidence: 99%